2019
DOI: 10.1186/s43043-019-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient and in vitro fertilization (IVF) cycle characteristics associated with variable blastulation rates: a retrospective study from the Duke Fertility Center (2013–2017)

Abstract: Background: To evaluate the association of patient and IVF cycle characteristics with blastulation rate and formation of high-quality blastocysts Results: We analyzed autologous blastocyst cycles from 2013 to 2017. Cycles were subdivided into low (< 33%), intermediate (33-66%), and high (> 66%) blastulation rates. Embryo quality was assigned by embryologists using Gardner Criteria. R statistical package was used, and the blastulation groups were compared using analysis of variance (ANOVA) for continuous variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In the present study, despite the higher number of retrieved and mature oocytes in the GnRHa group, blastocyst development rates were comparable between both COS regimens. These results again highlight the previously established notion that a higher oocyte yield is not associated with an improved blastocyst development rate [ 25 ]. Aggressive ovarian stimulation poses a serious risk of developing OHSS.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, despite the higher number of retrieved and mature oocytes in the GnRHa group, blastocyst development rates were comparable between both COS regimens. These results again highlight the previously established notion that a higher oocyte yield is not associated with an improved blastocyst development rate [ 25 ]. Aggressive ovarian stimulation poses a serious risk of developing OHSS.…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, the blastulation rate of group 3 was significantly higher when compared with group 2. Cycle characteristics alone may not be an accurate predictor for the rate of blastulation, as there have been many conflicting results reported in previous literature (Jones et al, 2020). It has been shown that better quality blastocysts are mostly generated by oocytes originating from a follicular volume of between 13 and 23 mm (Agrawal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, confounders exist such as timing of observation, culture medium, and culture conditions. This parameter was chosen because several studies emphasized the importance of these laboratory data in influencing clinical results [34,39,40]. We also established an assessment of the data by stratifying for maternal age as some studies reported that quantity and quality of blastocysts formed are independent from the number of collected oocytes, but negatively associated with female age [39].…”
Section: Proportion Of Embryos With ≥ 8 Cells On Daymentioning
confidence: 99%
“…This parameter was chosen because several studies emphasized the importance of these laboratory data in influencing clinical results [34,39,40]. We also established an assessment of the data by stratifying for maternal age as some studies reported that quantity and quality of blastocysts formed are independent from the number of collected oocytes, but negatively associated with female age [39]. In addition, several authors showed a maternal age-dependent effect on embryo development emerging only at the blastocyst stage [34,41,42].…”
Section: Proportion Of Embryos With ≥ 8 Cells On Daymentioning
confidence: 99%